Pengaruh Kualitas Layanan Elektronik Terhadap Loyalitas Pelanggan “Buka Lapak” Melalui Kepuasan Pelanggan ( Studi Kasus Di Kampus Ama Yogyakarta ) - Wahyudiyono Wahyudiyono (Jurnal Solusi, 2021)
Absract Increasingly competitive business requires entrepreneurs to make new innovations in service, like providing convenience to customers in making transactions. Through this effort, the company can maintain market share so that it exists. By utilizing internet media in the digital era today, one of the initiatives done is to provide electronic services to customers. The purpose of this research is to find out and test the influence of e-service quality on customer loyalty mediated by customer satisfaction variables. The population in this study was the students of the Academy of Administration Management Yogyakarta (AMAYO) of which they had transacted more than two times of the online shopping site Bukalapak. The sampling technique used was purposive sampling sample. The number of sampling was 100. Based on the results of research, e-service quality has positive influences for customer satisfaction and customer loyalty. Besides, it can be proven that customer satisfaction is the mediation of the quality of E-service influencing customer loyalty. Based on Sobel Formula, it was found that the value T calculated 3.97449 > T table 1.960. It means that E-Service Quality affects customer loyalty mediated by customer satisfaction. Further, it needs other research types of online shopping sites in Indonesia. Keywords: E-Service Quality, Customer Loyalty, Customer Satisfaction, Internet Marketing, Bukalapak